Assessing employability skills of technical and vocational education and training (TVET) graduates in Malaysia - Hii, Annie (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Nowadays, employers are seeking for good workers who are balanced with adequate technical skills and employability skills. However, most of our graduates still do not realize the importance of employability skills to the real working environment. As a result, the graduates are said to be had mastered the relevant technical skills, but they are lack of important employability skills such as basic skills, thinking skill, resource management skill, informational skills, interpersonal skill, system and technology skills and personal quality skills. The research was conducted to identify the level of employability skills among TVET graduates and to determine the differences of employability skills level based on students’ gender. Quantitative survey research design was used in this study and questionnaires were used to collect TVET students’ perceptions. The study is conducted at Universiti Pendidikan Sultan Idris and focused on the final year students of Faculty of Technical and Vocational Education, which are Bachelor in Agriculture Science, Living Skills and Home Economics. The instrument used was adapted and modified from Secretary’s Commission on Achieving Necessary Skills or SCANS (1991) in order to assess graduates’ employability skills. Both descriptive analysis and inferential analysis are used in this study to analyze the result. Besides, it is anticipated that this study will increase awareness and offer new perspectives among the general public on the important of employability skills needed by the university graduates to enter the job market. Therefore, this study was carried out to determine the level of employability skills owned by TVET graduates in Malaysia.